Study on Quality Uncertainty Prediction Model Based on Data and Its Application Management (Journal of Fiber Bioengineering and Informatics, 2015)
To predict textile quality fluctuation from the perspective of uncertainty factors, first, the reasons\rand patterns of quality fluctuation in the industrial textile processing were analyzed, and knowledge\rrepresentation of textile quality attributes was studied. Second, through the theories of human-machineenvironment-\rsystem-engineering (HMESE), probability, and statistics, the uncertainty factors that affect\rtextile production quality were extracted, and generation mechanism, interaction relationship and\rbehavioral characteristics of them was explored. Then, an improved human-machine-environment brittle\rmodel oriented to the textile processing was built. As verified by the experiment and simulation,\rthe results have shown that the improved brittle model has achieved a full range analysis of quality\runcertainty of the textile, which are from the reason and pattern of quality fluctuation to generation\rmechanism, mutual relations, and behavior identification of the uncertainty factors.
Keywords: Textile Processing; Prediction; Quality; Uncertainty